Sociodemographic factors associated with prenatal care utilization in Arkansas, United States - Pearl A. McElfish; Aaron Caldwell; Donya Watson; Jonathan Langner; Jennifer Callaghan-Koru; Austin Porter; Don E. Willis; Jennifer A. Andersen; Nicola L. Hawley; James P. Selig; Amir Forati; Maria R. Alcala; et al. (Preventive Medicine Reports)
Objectives: This study examines prenatal care utilization differences in Arkansas. Methods: Birth records data from the National Center for Health Statistics were used. The study population consisted of singleton live births in Arkansas from 2014 to 2022. Primary outcomes included number of prenatal visits, fewer than the recommended number of prenatal visits, late prenatal care, and no prenatal care. Summary statistics were computed, and adjusted rates ratios were calculated adjusting for maternal age, maternal education, and parity for payer, race/ethnicity, and rural/urban residence. Results: Mothers with a Medicaid-covered birth had 0.90 times fewer prenatal care visits and were 1.26 times more likely to have fewer than the recommended number of visits, 1.60 times more likely to initiate prenatal care late, and 1.46 times more likely to have reported no prenatal visits at all. Number of prenatal care visits was lower for all racial/ethnic groups relative to white mothers and for mothers living in rural areas. The largest differences were for Native Hawaiian and Pacific Islander (NHPI) mothers, who reported almost half the number of visits (ARR = 0.67, 95 % CI [0.64, 0.70]). Having no prenatal care was more prevalent among NHPI (ARR = 3.68, 95 % CI [2.66, 5.10]) and Black (ARR = 1.47, 95 % CI [1.34, 1.61]) mothers. Racially/ethnically minoritized groups were more likely to have late prenatal care and fewer than the recommended number of prenatal visits, with the greatest difference for NHPI. Conclusions: Findings document disparities in prenatal care utilization related to payer, race/ethnicity, and rural/urban residence.